PROGRAM OF EXERCISING WITH WEIGHTS AND SIMULATORS BY STATION METHOD ADAPTED TO FEMALES - Nebojša Čokorilo; Milena Mikalački; Darinka Korovljev (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Facility for exercising with weights, popularly called 'the gym'', is, in the opinion of majority of women, a place designed for men, a facility adapted to their needs. Also, they have a fear of losing their feminine characteristics, by increasing the muscular volume. In a word, they are afraid of effects opposite to those they expect to achieve with regular physical exercising. It is necessary to evade the "blind" copying of the trainings made exclusively for men onto women. On the other hand, when it is measured in terms force/cm², the area of cross-section, the muscle a woman can achieve almost the same maximal force as man's muscle - which is 3 and 4 kg/cm². Because of that, the greatest difference in total quality of muscles lies in additional percentages of the muscles of the male body, which is explained with endocrinal differences. Hormone differences between men and women are certainly the underlying cause of majority, if not, all differences in sport abilities. This model of exercising with weights and simulators was made taking into account the specific features of female exercising. Exercising is performed in the zone of the mid-load. Mid-load is calculated by defining the weight of the "load" for each exercise and examinee separately. Load varied within the range of 45% to 70% of the maximal one (under the term maximal, we mean maximal load that a gymnast manages to cope, making a specific move which is achieved by one repetition only). In the very beginning, and if we work with the total beginners, application of such way of load measuring is not recommendable, because some unfavourable effects might be caused. Due to that, such way of load calculating is delayed for the second month, while for the first month and based on the body value, each gymnast gets the weight 30% - 50% of load of her body weight. It all depends on their initial ability as well as the type of each specific exercise. The aim is to adjust the load to the extent at which each gymnast will be able to complete the given exercises, without stopping before the completion of the series. The program of exercising was applied three times under the same conditions, and gave good results in reduction of the fat tissue and increase of power within female population.